Development of a DDA+PGA-combined non-destructive active interrogation system in “Active-N″ - Kazuyoshi Furutaka; Akira Ohzu; Yosuke Toh (Nuclear Engineering and Technology, 2023)
An integrated neutron interrogation system has been developed for non-destructive assay of highly-radioactive special nuclear materials, to accumulate knowledge of the method through developing and using it. The system combines a differential die-away (DDA) measurement system for the quantification of nuclear materials and a prompt gamma-ray analysis (PGA) system for the detection of neutron poisons which disturb the DDA measurements; a common D-T neutron generator is used. A special care has been taken for the selection of materials to reduce the background gamma rays produced by the interrogation neutrons. A series of measurements were performed to test the basic performance of the system. The results show that the DDA system can quantify plutonium of as small as 20 mg and it is not affected by intense neutron background up to 1.57 × 107 s−1 and gamma ray of 4.43 × 1010 s−1. The gamma-ray background counting rate at the PGA detector was reduced down to 3.9 × 103 s−1 even with the use of the D-T neutron generator. The test measurements show that the PGA system is capable of detecting 0.783 g of boron and about 86.8 g of gadolinium in 30 min.